Patient selection for trials. (October 2017) - Wolinsky, Jerry S
The last several decades have witnessed considerable progress in our understanding of the pathogenesis, refining diagnostic criteria, and identifying therapies of value for modifying the course of relapsing forms of multiple sclerosis. While the pace of progress has lagged for those with progressive phase disease, this now seems to be changing. This review considers those characteristics of patients with primary progressive multiple sclerosis that may contribute to phase 3 trial success and identifies some of the thorny issues that remain ahead. The larger of the studies conducted thus far have sequentially informed our understanding of "pure" primary progressive disease, and also challenge both phase 3 and especially phase 2 trial designs and participant selection for investigations going forward. This may have particular relevance for testing therapeutics directed at neuroprotection and repair in the face of ongoing progression regardless of trial participant categorization using current conventional disease phenotypes.